DEVELOPMENT OF A DATA PROCESSING INFORMATION SYSTEM USING DATA MINING TECHNOLOGY - Balakayeva, Г.Т.; Darkenbayev, Д.К.; Kulachar, Д.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article presents the design and development of a data processing information system using DataMining technology. When processing the data, DataMining methods were used: logistic regression, random forest, decision trees, support vector machine, artificial neural network, the results were compared, analyzed and presented in a table. The developed information system, by processing structured, unstructured and semi-structured patient data, allows medical professionals to make accurate predictions regarding the health status of patients. An information system developed using machine learning algorithms performs processing based on several individual data. Previous data is taken from the database, analyzed, further processed, the algorithm with the best results is compared, and the algorithm with the best results is selected. The data processing information system allows users to obtain forecast results in real time. The authors plan to put the created information system into production and continue to supplement the research work in the future. An information processing system can be used to predict the level of knowledge of students in the field of education.